Latest Early Permian granitic magmatism in southern Inner Mongolia, China: Implications for the tectonic evolution of the southeastern Central Asian Orogenic Belt - Li, S.; Wilde, Simon; Wang, T.; Xiao, W.; Guo, Q. (Elsevier Inc., 2014)
Latest Early Permian (277-275Ma) magmatic episode is one of the most important tectono-magmatic events in southeastern Central Asian Orogenic Belt (CAOB), recording a tectonic transition from accretionary to post-accretionary evolution of the Paleo-Asian Ocean. The latest Early Permian granitoids along the Solonker suture zone in southern Inner Mongolia were emplaced between 275Ma and 277Ma as determined by SHRIMP zircon U-Pb dating. They are characterized by variable alkali contents, a range from calcic to slightly alkalic compositions, and are magnesian I-type granitoids. Their eNd(t) values from -0.4 to +3.1 record predominantly juvenile crustal sources with moderate involvement of old crustal components. Furthermore, these granitoids show positive zircon eHf(t) values of +7.6 to +10.7 that are also indicative of predominantly juvenile nature. Their high zircon d18O values of 6.29‰ to 8.13‰, suggest significant involvement of supracrustal materials in their generation. These characteristics imply they were derived from an already hybrid andesitic magma in active continental margin. The resultant composite magmas were finally attached (relaminated) to the lower crust, where they produced segregated melt, to rise with minor assimilation of supracrustal materials, and to form these granitic plutons. The outboard migration of continental arc in response to slab roll-back, from the Late Carboniferous to the latest Early Permian, and tectonic switching from this prolonged extension to the short-lived contraction resulting from slab break-off and final amalgamation of the southeastern CAOB in the Middle-Late Permian lead to efficient continental growth in the southeastern CAOB.